(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Background: Glaucoma is regarded as an optic neuropathy that causes vision loss and is typically asymptomatic until advanced stages. The objective of this study was to determine if patients with primary open-angle glaucoma experienced systemic hypertension (POAG). Methodology: Patients which were known cases of glaucoma and age >40 years, taking regular drugs or receiving anti-glaucoma therapy were included in the study. The measurement of intraocular pressure was made using Goldmann tonometry. Result: There were 61 males and 53 females out of 114 POAG patients in the study. Out of 61 males 72.1% had hypertension whereas 49.1% out of 53 females hypertension. A Highly significant association was observed between hypertension and IOP. Conclusion: There was no major correlation between fundamental hypertension and IOP expansion. There was no clear correlation with systemic hypertension in any of the other clinical and diagnostic measures of POAG.